2016
DOI: 10.1038/mp.2016.119
|View full text |Cite
|
Sign up to set email alerts
|

PARP-1 is required for retrieval of cocaine-associated memory by binding to the promoter of a novel gene encoding a putative transposase inhibitor

Abstract: Reward-related memory is an important factor in cocaine seeking. One necessary signaling mechanism for long-term memory formation is the activation of poly(ADP-ribose) polymerase-1 (PARP-1), via poly(ADP-ribosyl)ation. We demonstrate herein that auto-poly(ADP-ribosyl)ation of activated PARP-1 was significantly pronounced during retrieval of cocaine-associated contextual memory, in the central amygdala (CeA) of rats expressing cocaine-conditioned place preference (CPP). Intra-CeA pharmacological and short hairp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 53 publications
1
5
0
Order By: Relevance
“…This goes along with Szyf and colleagues' previous hypothesis that alterations in DNA epigenetics serve as a "genomic" memory of physiological and cognitive performance [37]. In a previous study we reported that PARP-1 is highly enriched in genes involved in various aspects of brain function, as well as in the acquisition and retrieval of cocaine-associated memory [20]. Due to PARP-1 epigenetic properties, along with our current results, we suggest conducting future research regarding possible epigenetic regulation in the CeA, in order to detect potential biomarkers associated with PTSD-like manifestation.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…This goes along with Szyf and colleagues' previous hypothesis that alterations in DNA epigenetics serve as a "genomic" memory of physiological and cognitive performance [37]. In a previous study we reported that PARP-1 is highly enriched in genes involved in various aspects of brain function, as well as in the acquisition and retrieval of cocaine-associated memory [20]. Due to PARP-1 epigenetic properties, along with our current results, we suggest conducting future research regarding possible epigenetic regulation in the CeA, in order to detect potential biomarkers associated with PTSD-like manifestation.…”
Section: Discussionsupporting
confidence: 77%
“…In previous research, we demonstrated the effect of PARP-1 activity in the CeA on cocaine-associated memory and conditioned place preference (CPP) with cocaine. We also demonstrated that inhibition of PARP-1 activity during cocaine-associated memory retrieval abolished CPP; compared to inhibition after memory retrieval, which did not affect the CPP reconsolidation process and subsequent retrievals [20].…”
Section: Introductionmentioning
confidence: 59%
“…1,2 Poly-ADP-ribosylation of DNA methyltransferase has been explored for its epigenetic effect, and for its possible role in de novo methylation in the central nervous system. 913…”
Section: Introductionmentioning
confidence: 99%
“…Previous findings by us and others indicate that Parp1 is necessary for forming and retrieving long-term memories of feeding, stress, and cocaine-seeking behaviors (Goldberg, Visochek, Giladi, Gozes, & Cohen-Armon, 2009; Hernández et al, 2009; E. Lax et al, 2017; Scobie et al, 2014).…”
Section: Introductionmentioning
confidence: 83%
“…We dissolved ABT-888 hydrochloride in saline and injected 15 mg/kg of ABT888 intraperitoneally at 0.1 ml volume. The injection took place 50 min before the FST based on pharmacokinetic experiments (Donawho et al, 2007) and as we reported before (Lax et al, 2017). Equal volumes of saline were injected to control mice.…”
Section: Methodsmentioning
confidence: 99%